The Internet show [videorecording] drivers' education for the information superhighway - Byrd, Phillip; Meek, John; Watts, Bill (Brandenburg Productions in association with the Production Companies, Inc., 1994)
Introduces the key to navigating the information superhighway via a clear-cut presentation of the system and a step-by-step guide towards the Internet.